Glass adhesive
A polysilazane-based adhesive with specific structures and a curing catalyst addresses UV-induced degradation and temperature limitations, ensuring strong and durable bonding for UV-LEDs.
Patent Information
- Application Number
- JP2021074397
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-04-26
AI Technical Summary
Existing adhesives used for UV-LEDs degrade under UV light, leading to cracks and voids, and require high temperatures for curing, limiting their durability and effectiveness in bonding materials.
A vitreous adhesive composed of a polysilazane compound with specific structures and a curing catalyst, which does not contain hydrosilyl groups, is developed, ensuring high UV resistance and sufficient bonding strength at low temperatures without causing cracks or voids.
The adhesive provides high UV resistance, maintains bond integrity through reflow processes, and prevents defects like cracks and voids, offering improved durability and reliability for UV-LED applications.
Smart Images

Figure 0007611757000001 
Figure 0007611757000002 
Figure 0007611757000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a vitreous adhesive. [Background technology]
[0002] In recent years, technology for irradiating UV light for purposes such as sterilization and cleaning has been developed. Specific examples include sterilization of places that patients touch, such as doorknobs and slippers in medical institutions, sterilization of wastewater in sewage treatment plants, decomposition and cleaning of organic matter attached to objects, and hardening of UV-curable resins. This is due to the effect of wavelengths in the UV range breaking the chemical bonds of organic matter and initiating radical polymerization reactions by catalysts.
[0003] Traditionally, UV was generally generated from mercury lamps, xenon lamps, metal halide lamps, etc., but with the recent development of LED technology, UV-LEDs have also become a candidate for UV irradiation sources. This is because the output of UV-LEDs has improved to a practical level, and because they have a higher light conversion efficiency and generate less heat than conventional light sources, they can save energy. In addition, high output is achieved not with a single lamp, but by equipping multiple UV-LED chips, so there is a great deal of freedom in terms of shape and size. These factors have led to an increase in demand for UV-LEDs.
[0004] Since LEDs generate light from a semiconductor chip, naturally, if the chip or the electrical circuits connected to the chip are damaged, the light emission intensity weakens, and in the worst case, they will not emit light at all. For this reason, it is common to use encapsulants to protect them and increase their durability. In addition to providing physical protection, encapsulants also protect the semiconductor chip and electrical circuits from harmful substances such as moisture and sulfide gas. Inexpensive epoxy resin is often used for this encapsulant, but in recent years, the increased power output of visible light LEDs has led to noticeable deterioration of epoxy resin due to light and heat caused by the heat generated by the chip, so silicone resin is increasingly being used.
[0005] Silicone resin has fewer carbon-carbon bonds, which are the main chain of organic resins such as epoxy resin, and is mainly composed of Si-O-Si siloxane bonds, which are more resistant to light and heat. Therefore, it has good light resistance and heat resistance, and is used for high-power LEDs. However, even silicone resin cannot withstand UV-LEDs, which irradiate UV, which has higher energy than these visible light LEDs, and a small amount of carbon-carbon bonds used during curing are broken and radicals are generated. These radicals form new cross-links, so the hardness of the silicone resin increases rapidly, and eventually cracks occur and it no longer functions as a sealant. For this reason, UV-LEDs do not use sealants, and instead a method has been proposed in which the light extraction surface of the LED is covered like a window with quartz glass, which is not altered by UV and has a high UV transmittance (for example, Patent Document 1). However, there is a problem that the adhesive used to attach this quartz glass window, if an organic resin or silicone resin is used, will deteriorate due to UV.
[0006] In order to solve this problem, UV-resistant silicone resins that minimize carbon-carbon bonds, which are particularly susceptible to UV degradation in silicone resins, have been proposed (for example, Patent Document 2). These UV-resistant silicone resins are mainly cured by condensation reactions. Normally, silicone resins are cured by bonding vinyl groups and hydrosilyl groups in the resin through an addition reaction, so carbon-carbon bonds remain in the resin after the reaction, and degradation proceeds through the above-mentioned mechanism. On the other hand, condensation reactions are characterized by the fact that hydroxyl groups or alkoxy groups are condensed together to cure the resin, so that no carbon-carbon bonds remain in the cured resin. Therefore, condensation curing is generally considered to have higher UV resistance than addition curing. However, condensation curing contains components such as water and alcohol that are eliminated during the condensation reaction. Since these are liquid at room temperature, if the condensation reaction is not allowed to proceed completely during the heat treatment for curing, the condensation reaction of unreacted groups will gradually proceed during use of the device, generating water and alcohol. This not only contributes to the deterioration of the device, but also causes defects such as cracks and voids in the adhesive resin when it is reheated due to some factor such as a reflow process, as it vaporizes and its volume increases dramatically.
[0007] Also, a method of using polysilazane resin instead of silicone resin has been proposed (for example, Patent Document 3). Like condensation-curing silicone resin, polysilazane resin does not have a carbon-carbon bond in the main chain, and curing is mainly due to dehydrogenation condensation of hydrosilyl groups. Since the component that is eliminated is hydrogen gas, the component that is eliminated is less likely to remain in the cured resin than condensation-curing silicone resin, and defects are less likely to occur. However, the dehydrogenation condensation of hydrosilyl groups in polysilazane has a large difference in interatomic distance before and after the bond, and large curing shrinkage stress occurs, so cracks are likely to occur. In addition, the dehydrogenation condensation of hydrosilyl groups requires a high temperature for curing even if a catalyst is used, and the reaction is often insufficient when cured at a low temperature. Therefore, there are restrictions such as the necessity for heat curing treatment, and the inability to use it on substrates with low heat resistance such as organic resins. Furthermore, polysilazane, which hardens through dehydrogenation condensation, exhibits high gas barrier properties because it takes on a dense structure when hardened; however, when used in a structure in which a film such as an adhesive is sandwiched between the polysilazane and the film, the hydrogen gas produced by the dehydrogenation condensation is prevented from escaping to the outside of the hardened film, just like condensation-curing silicone resins, and this causes voids.
[0008] On the other hand, polysilazane resins that have a curing mechanism that does not involve dehydrogenation condensation have also been proposed (for example, Patent Document 4). However, in the proposed method, in order to increase the adhesive strength, vulcanization is carried out by adding vulcanization accelerators such as dithiocarbamic acid metal salts and sulfenamides. This vulcanization is effective for bonding rubber, but when used to bond metals or ceramics, the substrate is vulcanized, which is a problem that makes it unusable in most cases.
[0009] Therefore, a method of melting and bonding with inorganic materials such as low-melting-point glass instead of these resins has been proposed (for example, Patent Document 5). Although this method can minimize the deterioration of LED devices due to UV rays, it has the problem of being very expensive.
[0010] In order to solve the above problems, there is a need for an adhesive that is low cost, has high UV resistance, bonds with sufficient strength at low temperatures, and does not produce voids, cracks, etc. even after a reflow process. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2019-186333 A [Patent Document 2] JP 2018-065938 A [Patent Document 3] Japanese Patent Application Publication No. 9-130065 [Patent Document 4] Japanese Patent Application Publication No. 53-026834 [Patent Document 5] JP 2018-192403 A Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention has been made in consideration of the above circumstances, and has an object to provide an adhesive that is low cost, has high UV resistance, and does not cause cracks or the like even after a reflow process. [Means for solving the problem]
[0013] The present invention has been made to achieve the above object, and provides a coating agent having the following characteristics. That is, the present invention provides: (A) a polysilazane compound having a structure represented by the following formula (A-1) or formula (A-2) and not containing a hydrosilyl group; and [ka] (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and in the polysilazane compound, R may be the same or different.) (B) Curing catalyst a molar ratio of the (A-1) component to the (A-2) component is within the range of (A-1):(A-2)=3:7 to 7:3, the non-volatile content of the composition is 50 mass% or more when heated at 105°C for 3 hours, and the curing catalyst is an organic acid, a d-block element belonging to the fourth period of the periodic table, a platinum group element, an amphoteric element, or a compound having these metal elements. A catalyst selected from the group consisting of The present invention provides a glass adhesive characterized by:
[0014] Such a glass adhesive is low cost, has high UV resistance, and does not cause cracks even after the reflow process.
[0015] In this case, it is preferable that R in the formula (A-1) is a methyl group.
[0016] When the polymer has such a structure represented by formula (A-1), the stability and workability of the produced polymer are improved.
[0017] In the present invention, R in the formula (A-2) is preferably a methyl group.
[0018] When the compound has a structure represented by such formula (A-2), the curing rate and the film properties after curing become more favorable.
[0019] In the present invention, the (B) curing catalyst is preferably citric acid or an organoaluminum compound.
[0020] If such a curing catalyst is contained, the curing reaction proceeds smoothly. Effect of the Invention
[0021] As described above, the glass adhesive of the present invention is a glass adhesive made of a composition containing a polysilazane compound having at least two types of structures and a curing catalyst, and it is possible to obtain an adhesive with high UV resistance at low cost. Furthermore, the glass adhesive of the present invention can bond with sufficient strength at low temperatures, and does not cause defects such as cracks even after the reflow process, so it exhibits high gas barrier properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] As mentioned above, there was a need to develop an adhesive that was low cost, had high UV resistance, bonded with sufficient strength at low temperatures, and did not produce voids or cracks after the reflow process.
[0023] Means for Solving the Problems The present inventors have conducted intensive research into the above-mentioned problems and have found that the above-mentioned problems can be solved by a glass adhesive comprising a composition containing a polysilazane compound having two specific different types of structures in a specific ratio and containing no hydrosilyl groups, and a specific curing catalyst, wherein the non-volatile content of the composition is a specific ratio or more, and have thus completed the present invention.
[0024] That is, the present invention provides: (A) a polysilazane compound having a structure represented by the following formula (A-1) or formula (A-2) and not containing a hydrosilyl group; and [ka] (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and in the polysilazane compound, R may be the same or different.) (B) Curing catalyst a molar ratio of the (A-1) component to the (A-2) component is within the range of (A-1):(A-2)=3:7 to 7:3, the non-volatile content of the composition is 50 mass% or more when heated at 105°C for 3 hours, and the curing catalyst is an organic acid, a d-block element belonging to the fourth period of the periodic table, a platinum group element, an amphoteric element, or a compound having these metal elements. A catalyst selected from the group consisting of The glass adhesive is characterized in that
[0025] The present invention will be described in detail below, but the present invention is not limited thereto.
[0026] <Glass adhesive> The glass adhesive of the present invention, as described below, comprises a composition containing, as component (A), a polysilazane compound having a structure represented by specific formula (A-1) and formula (A-2) and not containing a hydrosilyl group, and as component (B), a curing catalyst. This composition can contain additives such as a diluting solvent and a filler in addition to components (A) and (B). These components will be described below.
[0027] [(A) Polysilazane compound] The polysilazane compound used in the glass adhesive of the present invention is characterized by having two different structures and not containing a hydrosilyl group. The presence or absence of a hydrosilyl group (Si-H) in the polysilazane compound (polymer) is 1 For example, 0.02 ml of the polysilazane polymer was diluted to 3 ml with deuterated chloroform and analyzed by a 400 MHz NMR apparatus manufactured by Bruker. 1 H-NMR measurement can be performed. If a Si-H bond is present in the polysilazane polymer, a peak will be observed in the range of 4.0 to 5.5 ppm.
[0028] The different structures are (A-1) and (A-2), respectively, and are represented by the following formulas (A-1) and (A-2), respectively.
[0029] (A-1) The following formula (A-1) [ka] (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and in the polysilazane compound, R may be the same or different.)
[0030] The polysilazane structure (A-1) is a structure represented by the above formula (A-1) (hereinafter, also referred to as "component (A-1)"). In the formula, R may be, for example, a methyl group, an ethyl group, a vinyl group, a phenyl group, a methoxy group, an ethoxy group, etc., and may be the same or different within a molecule. Among them, from the viewpoint of the stability and workability of the generated polymer, R is preferably a methyl group. In addition, from the viewpoint of adhesion to an adherend and transparency due to a similar refractive index, when R contains an ethyl group, a vinyl group, a phenyl group, etc., the ratio of these groups to the total R is preferably 10 mol% or less, more preferably 5 mol% or less.
[0031] (A-2) The following formula (A-2) [ka] (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and in the polysilazane compound, R may be the same or different.)
[0032] The polysilazane structure (A-2) is a structure represented by the above formula (A-2) (hereinafter, also referred to as "component (A-2)"). In the formula, R may be, for example, a methyl group, an ethyl group, a vinyl group, a phenyl group, a methoxy group, an ethoxy group, etc., and may be the same or different within a molecule. Among them, from the viewpoint of the curing speed and the film properties after curing, R is preferably a methyl group. In addition, from the viewpoint of adhesion to an adherend and transparency due to a similar refractive index, when R contains an ethyl group, a vinyl group, a phenyl group, etc., the ratio of these groups to the total R is preferably 10 mol% or less, more preferably 5 mol% or less.
[0033] In the present invention, it is important that the (A-1) component and the (A-2) component are mixed in an appropriate ratio, taking into consideration the balance between workability, curing speed, and cured product properties. Specifically, the molar ratio of the (A-1) component and the (A-2) component must satisfy the range of (A-1):(A-2)=3:7 to 7:3. If it is within this range, the characteristics due to one polysilazane structure are not strongly reflected, and the characteristics due to the two types of polysilazane structures are expressed in a balanced manner, which is preferable. On the other hand, if the (A-1) component is more than this ratio, the stability of the polymer is high and the curing speed of the coating film is slow, making it unsuitable for use as an adhesive.
[0034] Furthermore, if the amount of (A-2) component is too large, not only will the curing speed be too fast, which may impair workability, but the polymerization will proceed during storage and gelation will occur, and the crack resistance will decrease, which may result in insufficient adhesive strength when used as an adhesive.
[0035] The molecular weight of the polysilazane compound is not particularly specified, but from the viewpoint of workability such as curing speed and viscosity, the weight average molecular weight is preferably within the range of 500 to 100,000. If the weight average molecular weight is 500 or more, curing proceeds quickly and the effect as an adhesive can be expected, and if it is 100,000 or less, the viscosity is easy to handle and there is no risk of curing during use, so it is preferable. The weight average molecular weight was measured using a GPC (gel permeation chromatography) device by the following method.
[0036] The synthesis method of the polysilazane compound having the polysilazane structure (A-1) and the polysilazane structure (A-2) is not particularly limited, and the compound can be synthesized by a known method (for example, the method described in Patent Documents 3 and 4). For example, a halogenated silane raw material (such as dimethyldichlorosilane) that gives the structure (A-1) and a halogenated silane raw material (such as methyltrichlorosilane) that gives the structure (A-2) are added to anhydrous pyridine so that the molar ratio (A-1):(A-2) of the (A-1) component and the (A-2) component is within a predetermined range, ammonia gas is blown into the liquid to cause a reaction, and further purification such as filtration and distillation is performed as necessary to obtain a polysilazane compound (so-called pyridine complex method).
[0037] In addition, tetrachlorosilane may be added as an optional component during synthesis of the polysilazane compound. The addition of tetrachlorosilane is expected to increase the molecular weight of the polysilazane compound, and can improve workability by shortening the curing time and adjusting the viscosity. When added, it is preferably added in an amount of 0 to 5 mol% of the total components (A-1) and (A-2).
[0038] [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.6mL / min Detector: UV detector Column: TSK Guardcolumn SuperH-L TSKgel SuperMultipore HZ-M (4.6mm I.D. x 15cm x 4) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (0.5 wt% THF solution)
[0039] [(B) Curing catalyst] The curing catalyst used in the present invention is a catalyst selected from the group consisting of organic acids, d-block elements belonging to the fourth period of the periodic table, platinum group elements, amphoteric elements, or compounds containing these metal elements, and is not particularly limited as long as it allows polymerization of the polysilazane compound used to proceed.
[0040] Specific examples of the curing catalyst include (i) organic acids such as carboxylic acids, such as formic acid, acetic acid, propionic acid, butyric acid, linoleic acid, linoleic acid, oleic acid, and oxalic acid, and hydroxycarboxylic acids, such as malic acid and citric acid, and (ii) simple metals selected from the group consisting of d-block elements belonging to the fourth period of the periodic table, such as titanium, manganese, cobalt, nickel, and zinc, platinum group elements, such as ruthenium, rhodium, palladium, osmium, iridium, and platinum, and amphoteric elements, such as aluminum, tin, and zinc, or compounds containing these metal elements. The curing catalyst of component (B) is preferably citric acid or an organoaluminum compound, with organoaluminum compounds being particularly preferred since the curing reaction proceeds even with the addition of a small amount, they are soluble in solvents, and they are not colored.
[0041] For example, examples of organoaluminum compounds include aluminum salts of organic acids such as aluminum carboxylate, aluminum alkoxides, and aluminum acetylacetonate complexes. Compounds having different anions or ligands, such as dibutoxy(2-oxo-5-oxa-3-hepten-4-yloxy)aluminum, may also be used.
[0042] The mixing ratio with the polysilazane compound is not particularly limited since it varies depending on the composition of the polysilazane compound and the type of curing catalyst added, but for example, in the case of an organoaluminum compound, it is preferably within the range of 0.01 to 5 parts by mass per 100 parts by mass of the polysilazane compound. Within this range, it has an excellent balance between curing speed and workability when used as an adhesive.
[0043] In the present invention, an organometallic compound such as an organoaluminum compound means an organic compound containing a metal, and includes not only compounds having a metal-carbon bond, but also organic compounds in which a heteroatom such as oxygen is bonded to a metal, and compounds in which a metal is bonded by an ionic bond, such as a salt of an organic acid.
[0044] [Other additives] In addition to the polysilazane compound and the curing catalyst, the glass adhesive of the present invention may contain additives such as a diluting solvent and a filler, if necessary.
[0045] Examples of dilution solvents include alkane compounds such as n-hexane, n-octane, and n-nonane, alkene compounds such as 1-octene, 1-nonene, and 1-decene, cycloalkane compounds such as cyclohexane, methylcyclohexane, and dimethylcyclohexane, ester compounds such as n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, isoamyl acetate, and ethyl caproate, and ether compounds such as diethyl ether, dibutyl ether, and ethylene glycol diethyl ether. The dilution solvent may be used to adjust the viscosity of the composition or to improve the wettability of the composition to the substrate, but the polysilazane compound A composition comprising It is necessary to ensure that the non-volatile content does not fall below 50% by mass when heated at 105°C for 3 hours. If it falls below 50% by mass, the diluent solvent is likely to remain in the cured product.
[0046] Examples of the filler include homogeneous or heterogeneous metal fillers containing metal elements such as magnesium, aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, zinc, gallium, zirconium, niobium, palladium, and platinum; reinforcing inorganic fillers such as fumed silica, fumed titanium dioxide, and fumed alumina; and non-reinforcing inorganic fillers such as fused silica, alumina, zirconium oxide, calcium carbonate, calcium silicate, titanium dioxide, ferric oxide, and zinc oxide.
[0047] Other additives include organosiloxane oligomers containing a functional group selected from a hydrosilyl group, an alkenyl group, an alkoxysilyl group, and an epoxy group, adhesion aids such as organooxysilyl-modified isocyanurate compounds and their hydrolysis condensates, and silicone oils such as dimethyl silicone and phenyl silicone, which can be added in any ratio depending on the required properties.
[0048] When the filler is a metal element selected from the group consisting of d-block elements belonging to the fourth period of the periodic table, platinum group elements, and amphoteric elements, or a compound containing these metal elements, it also functions as a curing catalyst, so that the content of the filler may be within the range of 0.01 to 5 parts by mass relative to 100 parts by mass of the polysilazane compound.
[0049] (Non-volatile content) The glass adhesive may contain volatile matters such as the dilution solvent and low molecular weight substances, but the non-volatile matter must be 50% by mass or more when the composition is heated at 105°C for 3 hours. If the non-volatile matter is less than 50% by mass, the volatile matter may remain in the cured product and adversely affect the physical properties. This is because if the volatile matter contains an organic compound with a carbon-carbon bond, it is prone to UV degradation, and because the volatile matter is liquid at room temperature, it vaporizes when reheated in a reflow process, etc., and the volume increases dramatically, causing defects such as cracks and voids in the adhesive resin. It is important to minimize the amount of volatile matter that may contribute to the deterioration of the device.
[0050] <Use of glass adhesive> Examples of methods for applying the glass adhesive of the present invention include roll coating methods using a chamber doctor coater, single roll kiss coater, reverse kiss coater, bar coater, reverse roll coater, forward rotation roll coater, blade coater, knife coater, etc., spin coating methods, dispensing methods, dipping methods, spraying methods, transfer methods, slit coating methods, etc.
[0051] There are no particular limitations on the substrate to be coated, and examples include organic synthetic resins such as polyethylene (PE), polyvinyl chloride (PVC), polystyrene (PS), polyvinyl acetate (PVAc), polyurethane (PUR), acrylonitrile butadiene styrene resin (ABS), acrylic resin (PMMA), polyamide (PA), nylon, polycarbonate (PC), polyethylene terephthalate (PET), polyimide (PI), and bismaleimide resin (BMI); silicone resins such as methyl silicone and phenyl silicone; metals such as aluminum, silicon, iron, nickel, copper, silver, and gold; oxides such as alumina, silica, titanium oxide, and zinc oxide; and nitrides such as boron nitride, aluminum nitride, silicon nitride, and gallium nitride.
[0052] The thickness of the coating film varies depending on the difference in linear expansion coefficient from the substrate and the temperature to which it is exposed, but is generally 0.1 to 100 μm, and preferably 0.5 to 50 μm in cured film thickness.
[0053] After forming an uncured polysilazane compound coating film by applying it to one or both of the members to be bonded in this way, it is preferable to heat and dry the coating film. This process is intended to completely remove the solvent and low molecular weight components contained in the coating film, but is not necessarily required if the coating film does not contain a solvent.
[0054] The heating and drying temperature is usually within the range of room temperature (25°C) to 300°C, preferably 70°C to 150°C. Preferred methods for the heating and drying process include heat treatment, microwave treatment, and infrared treatment. After the heating and drying process, the members to be bonded are pressed together to prevent air bubbles from being trapped, and then cured. Curing proceeds sufficiently even at room temperature, but it is possible to cure more quickly by heating. EXAMPLES
[0055] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, parts indicate parts by mass. The weight average molecular weight was measured under the above conditions. The non-volatile content is the mass % of the non-volatile content of each composition when it is heated at 105°C for 3 hours relative to the composition before heating.
[0056] To confirm that the polysilazane compound of component (A) does not contain a hydrosilyl group, check the Si-H in the polysilazane polymer. of 1 The measurement was performed using H-NMR analysis. 0.02 ml of polysilazane polymer was diluted to 3 ml with deuterated chloroform, and the measurement was performed using a 400 MHz NMR device manufactured by Bruker. 1 H-NMR measurement was performed. Note that, when Si-H bonds are present in the polysilazane polymer, a peak is observed in the range of 4.0 to 5.5 ppm.
[0057] [Examples 1-3, Comparative Examples 1-7] The adhesives shown in Table 1 were obtained using the polysilazane compound AH prepared by the following Synthesis Example AH. The adhesives obtained were evaluated as described below. Detailed data are shown in Table 1 below.
[0058] [Synthesis example A] 227g of methyltrichlorosilane and 456g of dimethyldichlorosilane were added to 4,000g of pyridine as halogenated silane raw materials, and ammonia gas was blown into the liquid at 1.0L / min for 390 minutes to cause a reaction. During this reaction, white ammonium chloride salt was produced and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off the pyridine, yielding polysilazane compound A. The weight average molecular weight of the polysilazane in this compound was measured and found to be 5,200.
[0059] [Synthesis example B] 378g of methyltrichlorosilane and 326g of dimethyldichlorosilane were added to 4,000g of pyridine as halogenated silane raw materials, and ammonia gas was blown into the liquid at 1.0L / min for 430 minutes to cause a reaction. During this reaction, white ammonium chloride salt was produced and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off the pyridine, yielding polysilazane compound B. The weight average molecular weight of the polysilazane in this compound was measured and found to be 8,700.
[0060] [Synthesis example C] 529g of methyltrichlorosilane and 196g of dimethyldichlorosilane were added to 4,000g of pyridine as halogenated silane raw materials, and ammonia gas was blown into the liquid at 1.0L / min for 460 minutes to cause a reaction. During this reaction, white ammonium chloride salt was produced and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off the pyridine, yielding polysilazane compound C. The weight average molecular weight of the polysilazane in this compound was measured and found to be 9,800.
[0061] [Synthesis example D] 378g of methyltrichlorosilane and 291g of monomethyldichlorosilane were added to 4,000g of pyridine as halogenated silane raw materials, and ammonia gas was blown into the liquid at 1.0L / min for 400 minutes to cause a reaction. During this reaction, white ammonium chloride salt was produced and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off pyridine, yielding polysilazane compound D. The weight average molecular weight of the polysilazane in this compound was measured and found to be 10,200.
[0062] [Synthesis example E] 291g of monomethyldichlorosilane and 255g of dichlorosilane were added to 4,000g of pyridine as halogenated silane raw materials, and ammonia gas was blown into the liquid at 1.0L / min for 340 minutes to cause a reaction. During this reaction, white ammonium chloride salt was produced and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off the pyridine, yielding polysilazane compound E. The weight-average molecular weight of polysilazane in this compound was measured and found to be 1,500.
[0063] [Synthesis example F] 756g of methyltrichlorosilane was added to 4,000g of pyridine as a halogenated silane raw material, and ammonia gas was blown into the liquid at 1.0L / min for 510 minutes to cause a reaction. During this reaction, white ammonium chloride salt was produced and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off the pyridine, yielding polysilazane compound F. The weight average molecular weight of the polysilazane in this compound was measured and found to be 25,100.
[0064] [Synthesis example G] 151g of methyltrichlorosilane and 522g of dimethyldichlorosilane were added to 4,000g of pyridine as halogenated silane raw materials, and ammonia gas was blown into the liquid at 1.0L / min for 380 minutes to cause a reaction. During this reaction, white ammonium chloride salt was produced and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off the pyridine, yielding polysilazane compound G. The weight average molecular weight of the polysilazane in this compound was measured and found to be 1,100.
[0065] [Synthesis example H] 605g of methyltrichlorosilane and 131g of dimethyldichlorosilane were added to 4,000g of pyridine as halogenated silane raw materials, and ammonia gas was blown into the liquid at 1.0L / min for 480 minutes to cause a reaction. During this reaction, white ammonium chloride salt was produced and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off the pyridine, yielding polysilazane compound H. The weight average molecular weight of the polysilazane in this compound was measured and found to be 7,800.
[0066] [Example 1] 70 parts of the polysilazane compound A obtained in Synthesis Example A, 26 parts of dibutyl ether, 0.07 parts of dibutoxy (2-oxo-5-oxa-3-hepten-4-yloxy) aluminum (Kelope EB-2: Hope Pharmaceutical Co., Ltd.), and 3.93 parts of ethanol were mixed in a vacuum degassing mixer for 5 minutes to obtain adhesive A. This adhesive A was applied to an alumina plate with a thickness of 1 mm, heated at 100°C for 10 minutes, and dried. Then, a glass plate with a thickness of 0.5 mm was pressed from above so as not to trap air bubbles, and the plate was left to stand at 25°C and a humidity of 40% for 24 hours to bond the plate. The sample after standing was firmly bonded, and no voids or cracks were observed. Furthermore, a reflow test was performed, and no change in appearance was observed before and after the reflow test. In addition, a UV irradiation test was performed on a sample in which an alumina plate and a quartz glass plate were bonded using the same method, but no deterioration due to UV was observed.
[0067] [Example 2] 70 parts of the polysilazane compound B obtained in Synthesis Example B, 26 parts of dibutyl ether, 0.07 parts of dibutoxy (2-oxo-5-oxa-3-hepten-4-yloxy) aluminum (Kelope EB-2: Hope Pharmaceutical Co., Ltd.), and 3.93 parts of ethanol were mixed for 5 minutes in a vacuum degassing mixer to obtain adhesive B. This adhesive B was applied to an alumina plate with a thickness of 1 mm, heated at 100°C for 10 minutes, and dried. Then, a glass plate with a thickness of 0.5 mm was pressed from above so as not to trap air bubbles, and the plate was left to stand at 25°C and a humidity of 40% for 24 hours to bond the plate. The sample after standing was firmly bonded, and no voids or cracks were observed. Furthermore, a reflow test was performed, and no change in appearance was observed before and after the reflow test. In addition, a UV irradiation test was performed on a sample in which an alumina plate and a quartz glass plate were bonded using the same method, but no deterioration due to UV was observed.
[0068] [Example 3] 70 parts of the polysilazane compound C obtained in Synthesis Example C, 26 parts of dibutyl ether, 0.07 parts of dibutoxy (2-oxo-5-oxa-3-hepten-4-yloxy) aluminum (Kelope EB-2: Hope Pharmaceutical Co., Ltd.), and 3.93 parts of ethanol were mixed in a vacuum degassing mixer for 5 minutes to obtain adhesive C. This adhesive C was applied to an alumina plate with a thickness of 1 mm, heated at 100°C for 10 minutes, and dried. Then, a glass plate with a thickness of 0.5 mm was pressed from above so as not to trap air bubbles, and the plate was left to stand at 25°C and a humidity of 40% for 24 hours to bond the plate. The sample after standing was firmly bonded, and no voids or cracks were observed. Furthermore, a reflow test was performed, and no change in appearance was observed before and after the reflow test. In addition, a UV irradiation test was performed on a sample in which an alumina plate and a quartz glass plate were bonded using the same method, but no deterioration due to UV was observed.
[0069] [Comparative Example 1] 70 parts of the polysilazane compound D obtained in Synthesis Example D, 26 parts of dibutyl ether, 0.07 parts of dibutoxy (2-oxo-5-oxa-3-hepten-4-yloxy) aluminum (Kelope EB-2: Hope Pharmaceutical Co., Ltd.), and 3.93 parts of ethanol were mixed in a vacuum degassing mixer for 5 minutes to obtain adhesive D. This adhesive D was applied to an alumina plate with a thickness of 1 mm, heated at 100°C for 10 minutes, and dried. Then, a glass plate with a thickness of 0.5 mm was pressed from above to prevent air bubbles from being trapped, and the plate was left to stand at 25°C and a humidity of 40% for 24 hours to bond the plate. After standing, the sample was firmly bonded, but voids had occurred in the adhesive layer. Furthermore, when a reflow test was performed, the adhesive layer peeled off after the reflow test. In addition, when a sample in which an alumina plate and a quartz glass plate were bonded using the same method was subjected to a UV irradiation test, cracks had occurred in the adhesive layer.
[0070] [Comparative Example 2] 70 parts of the polysilazane compound E obtained in Synthesis Example E, 26 parts of dibutyl ether, 0.07 parts of dibutoxy(2-oxo-5-oxa-3-hepten-4-yloxy)aluminum (Kelope EB-2: Hope Pharmaceuticals), and 3.93 parts of ethanol were mixed for 5 minutes in a vacuum degassing mixer to obtain adhesive E. Ewas applied to an alumina plate with a thickness of 1 mm, and dried by heating at 100°C for 10 minutes. After that, a 0.5mm thick glass plate was pressed onto the sample from above, taking care not to trap air bubbles, and the sample was left to stand for 24 hours at 25°C and 40% humidity. After standing, the sample was not bonded, and cracks had appeared in the adhesive layer. As the sample was not bonded, a reflow test and a UV irradiation test were not performed.
[0071] [Comparative Example 3] 70 parts of the polysilazane compound F obtained in Synthesis Example F, 26 parts of dibutyl ether, 0.07 parts of dibutoxy(2-oxo-5-oxa-3-hepten-4-yloxy)aluminum (Kelope EB-2: Hope Pharmaceuticals), and 3.93 parts of ethanol were mixed for 5 minutes in a vacuum degassing mixer to obtain adhesive F. F When applied to an alumina plate with a thickness of 1 mm, the solution gelled before the solvent dried. Since the sample was not bonded, the reflow test and UV irradiation test were not performed.
[0072] [Comparative Example 4] 70 parts of polysilazane compound B obtained in Synthesis Example B, 26 parts of dibutyl ether, 0.35 parts of concentrated sulfuric acid, and 3.65 parts of ethanol were mixed for 5 minutes in a vacuum degassing mixer to obtain adhesive B2. This adhesive B2 was applied to an alumina plate with a thickness of 1 mm, heated at 100°C for 10 minutes, and dried, whereupon it rapidly hardened and whitened. Adhesive B2 then gelled. Reflow tests and UV irradiation tests were not performed because the samples were not bonded.
[0073] [Comparative Example 5] 40 parts of the polysilazane compound B obtained in Synthesis Example B, 56 parts of dibutyl ether, 0.07 parts of dibutoxy (2-oxo-5-oxa-3-hepten-4-yloxy) aluminum (Kelope EB-2: Hope Pharmaceutical Co., Ltd.), and 3.93 parts of ethanol were mixed in a vacuum degassing mixer for 5 minutes to obtain adhesive B3. This adhesive B3 was applied to an alumina plate with a thickness of 1 mm, heated at 100°C for 10 minutes, and dried. Then, a glass plate with a thickness of 0.5 mm was pressed from above so as not to trap air bubbles, and the plate was left to stand at 25°C and a humidity of 40% for 24 hours to bond the plate. After standing, the sample was bonded, but the strength was insufficient and it was easy to peel off. In addition, the adhesive layer had a slight solvent odor. Furthermore, when a reflow test was performed, voids were generated. In addition, when a sample in which an alumina plate and a quartz glass plate were bonded using the same method was subjected to a UV irradiation test, discoloration was confirmed in the UV-irradiated area.
[0074] [Comparative Example 6] 70 parts of the polysilazane compound G obtained in Synthesis Example G, 26 parts of dibutyl ether, 0.07 parts of dibutoxy(2-oxo-5-oxa-3-hepten-4-yloxy)aluminum (Kerope EB-2: Hope Pharmaceutical Co., Ltd.), and 3.93 parts of ethanol were mixed for 5 minutes in a vacuum degassing mixer to obtain adhesive G. This adhesive G was applied to an alumina plate with a thickness of 1 mm, heated at 100°C for 10 minutes, and dried. Thereafter, a glass plate with a thickness of 0.5 mm was pressed from above so as not to trap air bubbles, and the plate was left to stand at 25°C and a humidity of 40% for 24 hours to bond the plate. After standing, the sample was barely cured and did not bond at all. Since the sample did not bond, a reflow test and a UV irradiation test were not performed.
[0075] [Comparative Example 7] 70 parts of the polysilazane compound H obtained in Synthesis Example H, 26 parts of dibutyl ether, 0.07 parts of dibutoxy(2-oxo-5-oxa-3-hepten-4-yloxy)aluminum (Kelope EB-2: Hope Pharmaceuticals), and 3.93 parts of ethanol were mixed for 5 minutes in a vacuum degassing mixer to obtain adhesive H. When this adhesive H was applied to an alumina plate with a thickness of 1 mm, the solution gelled before the solvent dried. Since the sample was not bonded, a reflow test and a UV irradiation test were not performed.
[0076] <Evaluation> Examples and Comparative Examples are summarized in Table 1. In addition, in the item of adhesion after standing for 24 hours at 25°C and 40% humidity, if the sample did not peel off when pulled strongly by hand, it was marked with ◯, if the sample adhered but peeled off when pulled by hand, it was marked with △, and if the sample did not adhere, it was marked with ×.
[0077] [Reflow test] A reflow test was carried out on the alumina-glass bonded samples produced in the examples and comparative examples using a reflow device manufactured by Tamura Corporation. The reflow conditions were that the samples were passed once through a 2m-distance furnace heated stepwise to 150°C, 200°C, 220°C, 260°C, and 265°C on a conveyor at a speed of 0.35m / min. The appearance was then checked.
[0078] [UV irradiation test] A sample was prepared by bonding an alumina plate and a quartz glass plate in the same manner as the alumina-glass bonded samples prepared in the Examples and Comparative Examples, and was irradiated with UV light of 285 nm wavelength and 45 mW output from the quartz glass side at an irradiation distance of 3 cm for 168 hours using a UV-B irradiation device manufactured by Nikkiso. After that, the appearance was confirmed.
[0079] In addition, if the reflow test and UV irradiation test were not performed, "-" is entered.
[0080] [Table 1]
[0081] In the table, the column for the raw material name (A-1) of the raw material halogenated silane shows the raw material halogenated silane (raw material (A-1)) that gives the structure (A-1), and the column for the raw material name (A-2) shows the raw material halogenated silane (raw material (A-2)) that gives the structure (A-2), along with their respective molar ratios. Since the condensation reaction proceeds quantitatively in the above synthesis example, the molar ratio (A-1):(A-2) of the (A-1) component and the (A-2) component of the prepared polysilazane compound can be considered to be consistent with the above molar ratio, that is, the charge ratio (raw material (A-1):(A-2) raw material).
[0082] In Examples 1 to 3 and Comparative Example 1, adhesion was strong enough after standing for 24 hours at 25°C and 40% humidity. Furthermore, in Examples 1 to 3, no defects in appearance occurred after adhesion. On the other hand, in Comparative Example 1, many voids occurred in the adhesive after adhesion. This is thought to be due to the dehydrogenation condensation reaction of the hydrosilyl group derived from monomethyldichlorosilane, generating hydrogen gas.
[0083] In addition, even after standing for 24 hours at 25°C and 40% humidity, the adhesive strength was insufficient in Comparative Example 5, and there was no adhesion in Comparative Examples 2, 3, 4, 6, and 7. Among them, Comparative Examples 5 and 6 did not have poor appearance, but Comparative Example 2 had peeling and cracks in the adhesive layer. This is presumably due to the curing shrinkage of the adhesive coating caused by the dehydrogenation condensation reaction of the hydrosilyl group derived from monomethyldichlorosilane. In addition, the adhesive layer gelled in Comparative Examples 3, 4, and 7. This is a phenomenon that occurs when there are many polymer structures derived from methyltrichlorosilane or when the catalyst is too strong, and the curing proceeds before the solvent evaporates, resulting in the solvent being taken up into the polymer.
[0084] In the reflow test, no change was observed in the cured film before and after the test in Examples 1 to 3. On the other hand, in Comparative Example 1, the adhesive layer peeled off from the substrate after the test. Also, in Comparative Example 5, voids were generated between the adhesive layer and the substrate. In the other Comparative Examples, the reflow test was not performed because a sufficient cured film was not obtained.
[0085] In the UV test, in Examples 1 to 3, no change was observed in the adhesive layer even after the test, and sufficient adhesive strength and transparency were maintained. However, in Comparative Example 1, cracks occurred in the adhesive layer, and the adhesive strength was reduced. In Comparative Example 5, brown coloring occurred in the UV-irradiated part. This is thought to be due to remaining solvent. In the other Comparative Examples, the UV test was not performed because a sufficient cured film was not obtained.
[0086] From these findings, the glass adhesive of the present invention is an adhesive that does not essentially contain carbon-carbon bonds that are severely degraded by UV rays, and does not contain any components that remain in the system even when cured. As a result, as can be seen from the above results, it can be said that it can be used as an adhesive more easily than conventional glass bonding, etc.
[0087] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.
Claims
1. (A) a polysilazane compound having a structure represented by the following formula (A-1) and a structure represented by the following formula (A-2) and not containing a hydrosilyl group; and 【Chemistry 1】 (B) Curing catalyst a molar ratio of the component (A-1) to the component (A-2) being within a range of (A-1):(A-2)=3:7 to 7:3, the non-volatile content of the composition being 50 mass% or more when heated at 105°C for 3 hours, and the curing catalyst being an organic acid, a d-block element belonging to Period 4 of the Periodic Table, a platinum group element, an amphoteric element, or a compound having these metal elements; A glass adhesive, characterized in that R in the formula (A-1) is a methyl group, and R in the formula (A-2) is a methyl group.
2. 2. The vitreous adhesive according to claim 1, wherein the curing catalyst (B) is citric acid or an organoaluminum compound.
Citation Information
Patent Citations
Polysilazane adhesive composition for silicone rubber
JP1978026834A
Catalytic treatment of polysilazane averagely containing at least two aliphatic unsaturated hydrocarbon group per one molecule
JP1987131031A
Production of organosilazane polymer and production of ceramics using said polymer
JP1987290730A
Electroluminescent element
JP1996236274A
Method of using ceramic precursor polymer as adhesive agent of electronic part
JP1997130065A